2017
DOI: 10.3389/fphar.2017.00837
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Eosinophil-Induced Bronchial Epithelial-Mesenchymal Transition with a Geranyl Acetophenone in a Coculture Model

Abstract: Epithelial-mesenchymal transition (EMT) is currently recognized as the main cellular event that contributes to airway remodeling. Eosinophils can induce EMT in airway epithelial cells via increased transforming growth factor (TGF)-β production. We assessed the effect of synthetic 2,4,6-trihydroxy-3-geranyl acetophenone (tHGA) upon eosinophil-induced EMT in a cellular model. The human eosinophil cell line EoL-1 was used to induce EMT in BEAS-2B human bronchial epithelial cells. The induction of EMT was dose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…The anti-inflammatory activity of tHGA has been demonstrated by various in vitro and in vivo studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. This is the first report on the anti-inflammatory effects of tHGA in alveolar epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory activity of tHGA has been demonstrated by various in vitro and in vivo studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. This is the first report on the anti-inflammatory effects of tHGA in alveolar epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo studies have established its anti-inflammatory activity in a range of cellular and disease models [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In particular, tHGA displays therapeutic potential for the treatment of asthma, a chronic inflammatory airway disease, owing to its anti-inflammatory activity and ability to attenuate airway remodeling [ 12 , 14 , 17 ]. Recently, tHGA demonstrated protective effects against vascular endothelial barrier dysfunction, suggesting its therapeutic potential in treating vascular inflammatory disorders [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that HMGB1 induces epithelial-mesenchymal transition (EMT) in airway epithelial tissue [19,20]. EMT, the transition of epithelial and endothelial cells to a motile phenotype, namely, transformation to mesenchymal stem cells, which not only associated with embryonic development, inflammation, tissue regeneration, and tumor formation, but also play an important role in the pathogenesis of ECRSwNP [21][22][23]. At the molecular level, epithelial cells lose their epithelial character and gain mesenchymal properties.…”
Section: Ivyspringmentioning
confidence: 99%
“…To date, various pharmacological activities of tHGA have been discovered. These include anti-inflammatory ( Shaari et al, 2011 ), endothelial and epithelial barrier protective ( Chong et al, 2016 ; Sim et al, 2018 ; Chan et al, 2021 ), anti-asthmatic ( Ismail et al, 2012 ; Lee et al, 2017a ; Lee et al, 2017b ; Yap et al, 2018 ; Ismail et al, 2019 ), anti-allergic ( Tan et al, 2017a ; Tan et al, 2017b ), and anti-cancer ( Cho et al, 2012a ; Cho et al, 2012b ) activities. Therefore, this mini review aims to summarize the reported pharmacological activities of tHGA and the underlying signaling pathways, as well as to pinpoint the potentials of this compound for drug development processes in the future.…”
Section: Introductionmentioning
confidence: 99%